What do we really know about the role of caffeine on urinary tract symptoms? A scoping review on caffeine consumption and lower urinary tract symptoms in adults. Issue 5 (9th April 2020) - Le Berre, Mélanie; Presse, Nancy; Morin, Mélanie; Larouche, Maryse; Campeau, Lysanne; Hu, Yu Xin; Reid, Isabelle; Dumoulin, Chantale
Abstract: Aims: The purpose of this scoping review was to map out the existing literature on caffeine intake and lower urinary tract symptoms (LUTS) in adults. Methods: In this scoping review, we searched for all studies available until June 2019 in MEDLINE, Embase, CINAHL, Cochrane Central Register, PsycINFO, LILACS, LiSSa, Web of Science, and Joanna Briggs Institute electronic databases, in addition to a hand search of the bibliographies of all relevant articles and a gray literature search. Both intervention studies on the effects of caffeine reduction in adults with LUTS and observational studies on the association between caffeine intake and LUTS‐related outcomes in adults were included and assessed for methodological quality by two independent reviewers. Results: Fourteen intervention and 12 observational studies were included. Overall, there was a decrease in urgency episodes (level of evidence 2, grade of recommendation B) and nocturnal enuresis episodes (4, C) with caffeine reduction. Observational studies reported an unclear association between caffeine intake and LUTS‐related outcomes. Most importantly, this present review highlighted high heterogeneity in the studied populations, caffeine measures, and reported outcomes. There was also unknown or high risk of bias in most identified studies. Conclusions: Caffeine reduction appears to reduce LUTS. Future studies on caffeine reduction interventions should target populations with urgency and urge urinary incontinence, which show the most promising results, and include valid and reliable measures of caffeine intake and LUTS. Finally, future studies should also use reporting guidelines to ensure lower risk of bias.